Komunikasi Efektif Dalam Keluarga PKK RW 09 Prima Harapan Regency - Armelsa, Dhefine; Risyan, Faqihar; Muhariani, Wulan; Wulandari, Sri (Jurnal Abdimas Komunikasi dan Bahasa, 2022)
The concept of family is very dependent on the social context in which the theory or concept of family is born. In Western society, families can be formed either with or without legal marriage ties, in Eastern culture, what is called a family are those who are bound by legal marriage ties. Families also determine how forms of communication are agreed upon and eventually form a certain pattern that distinguishes one family from another. The form of effective communication shows an identification to access communication behavior in a system. If the forms of effective communication mentioned above are associated with forms of family communication, then parents must provide good habituation to children so that they are instilled and form a good personality, provide good education in the family, school and community environment, and carry out effective communication activities between parents and children. Parents and children so that unwanted things don't happen. However, not all PKK mothers understand the various functions of effective communication within the family. To understand family communication patterns, it is also necessary to know several aspects related to the family, such as the type of family and at what level is the family as a community group.